1982
DOI: 10.1111/j.1471-0528.1982.tb05036.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of gestational age of the Asian fetus by the sonar measurement of crown‐rump length and biparietal diameter

Abstract: Summary. Two populations of pregnant Asian and European women were scanned using linear array real‐time ultrasound machines. Measurements were made of fetal crown‐rump length (CRL) up to 14 weeks gestational age and of biparietal diameter (BPD) up to 20 weeks gestational age. Polynomial growth curves relating CRL and BPD measurements to their gestational ages were fitted to the data by the method of unweighted least squares. There were no significant differences between the Asian and European parameters for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1983
1983
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…Prior studies have also evaluated the influence of maternal race on different types of fetal biometry. According to Parker et al, 7 measurements of the crown-rump length and biparietal diameter are similar for Asian and white fetuses up to 20 weeks. Lai and Yeo, 8 on the other hand, demonstrated slightly smaller biparietal diameter, head circumference, abdominal circumference, and femur length-more pronounced over the course of gestation-in Asian compared with white fetuses.…”
Section: Discussionmentioning
confidence: 95%
“…Prior studies have also evaluated the influence of maternal race on different types of fetal biometry. According to Parker et al, 7 measurements of the crown-rump length and biparietal diameter are similar for Asian and white fetuses up to 20 weeks. Lai and Yeo, 8 on the other hand, demonstrated slightly smaller biparietal diameter, head circumference, abdominal circumference, and femur length-more pronounced over the course of gestation-in Asian compared with white fetuses.…”
Section: Discussionmentioning
confidence: 95%
“…Otherwise, the MSLL measurement was used. Although previous studies have indicated that both linear 13,16 and linear-quadratic [13][14][15][17][18][19][20][21] functions are capable of describing the growth of fetal length during the first trimester, only linear (y = a0 + a1(x)) and quadratic (y = a0 + a1(x 2 )) functions were fitted to all fetal length (dependent variable)-menstrual age (independent variable) pairs from individual fetuses by the method of least squares 25 . Both of the functions had very high R 2 values (> 96-98%) in individual fetuses and their use permitted simple comparisons of slope values.…”
Section: Discussionmentioning
confidence: 99%
“…As with other anatomical measurements that change with age, the data on fetal length and age can be used to establish methods for determining the age of the fetus or for defining fetal growth standards. Nine of the previous publications are concerned with age determination [3][4][5][6][7][8][9][10][11] , seven with growth evaluation [12][13][14][15][16][17][18] and four with both 1,[19][20][21] . Of these investigations, only six have indicated that multiple measurements from individual fetuses were obtained 1,4,7,11,13,15 and in only one case 13 was the growth of individual fetuses characterized.…”
Section: Introductionmentioning
confidence: 99%
“…The gestational ages of the Chinese fetuses studied ranged from [16][17][18][19][20] weeks. The observed femur length measurements were compared with the corresponding data in Hadlock's chart with the Student's t test.…”
Section: Resultsmentioning
confidence: 99%